ANALYSIS OF THE EFFECT OF RETURN ON ASSET (ROA), OPERATIONAL COSTS AND OPERATING INCOME (BOPO) ON MUDHARABAH PROFIT SHARING IN SHARIA GENERAL TIRES FOR THE 2015-2020 PERIOD - Tika Enggal Saputri, Dedek; Mailindra, Wiyan; Sumanti, Eva (Asian Journal of Islamic Economic Studies, 2024)
This study aims to determine the retrun on asset (ROA) and operational costs and operating income (BOPO) on the profit sharing of mudharabah in Islamic commercial banks in Indonesia. The population uset in the study were 30 banks listed on the IDX and the total sample used 7 banks. In determining the sample, it uses random sampling with the criteria of Islamic banks that issue complete financial statement from 2015-2020. The analysis technique in this research is multiple analysis technique in order to get a comprehensiv picture between the relationship between one variable and another variable. In addition, the hypothesis test used is the t-test and f-test. Classical assision test which includes normality test, multicolinearity tets, heteroscedasticity test and autoccorelation tets were also used in this study. The results in this study show that the retrun on asset does not significantly affect the profit sharing of mudharabah, while operating costs and operating income also have no significant effect on the profit sharing of mudharabah. Keywords: Mudharabah Profit Sharing; Operating Costs; Operating Income; Retrun On Asset